The Regulator PltZ Regulates a Putative ABC Transporter System PltIJKNOP of Pseudomonas aeruginosa ATCC 27853 in Response to the Antimicrobial 2,4-Diacetylphloroglucinol - Guo, Ding-Ding; Luo, Li-Ming; Ma, Hai-Long; Zhang, Si-Ping; Xu, Hang; Zhang, Honghua; Wang, Yong; Yuan, Yongna; Wang, Zhen; He, Yong-Xing (Frontiers in Microbiology, 2020)
Pseudomonas aeruginosa is an opportunistic pathogen commonly infect immuno-compromised patients with diseases like cystic fibrosis (CF) and cancers and have high rates of recurrence and mortality. The treatment efficacy can be significantly worsened by the multidrug resistance (MDR) of P. aeruginosa and there is increasing evidence showing that this pathogen is easy to develop multidrug resistance. Here, we identified a gene cluster pltZ-pltIJKNOP, which was originally assumed to be involved in the biosynthesis of an antimicrobial pyoluteorin, significantly contributes to antibiotic resistance of Pseudomonas aeruginosa ATCC 27853. Moreover, the TetR-family regulator PltZ binds to a semi-palindromic sequence in the promoter region of the pltIJKNOP operon and recognizes the antimicrobial diacetylphloroglucinol (2,4-DAPG), which in turn induces the expression of the pltIJKNOP operon. Using quantitative proteomics method, we demonstrated that the regulator PltZ also plays an important role in maintaining metabolic hemostasis by regulating the transporting systems of amino acids, glucose, metal ions and bacteriocins. Taken together, our findings suggest a novel molecular mechanism by which P. aeruginosa can easily acquire a multidrug-resistant phenotype.